Firm Size and Liquidity Shape Profitability: Evidence from IDX Consumer Cyclicals (2021–2025) - Indah Damayanti; Indri Ayu Tansar (LPPM STMIK Mardira Indonesia, 2026)
While the consumer cyclicals sector heavily depends on macroeconomic shifts and fluctuating consumer purchasing power, many businesses struggle to maintain optimal profitability during volatile economic transitions. This study investigates how firm size and liquidity actively drive profitability among consumer cyclical companies listed on the Indonesia Stock Exchange (IDX) from 2021 to 2025. Employing a quantitative research design, we applied purposive sampling techniques to select a final sample of 16 qualified companies. Data analysis utilized multiple linear regression to examine the distinct impacts of corporate scale and short-term financial health on overall net returns. The empirical results reveal that firm size does not influence corporate profitability, suggesting that larger asset bases do not automatically guarantee superior financial returns in this specific sector. Conversely, liquidity significantly and directly impacts profitability, demonstrating that efficient short-term asset management and robust cash flows dictate a firm’s ultimate bottom-line success. This research introduces novelty by shifting focus toward the post-pandemic stabilization era (2021–2025), capturing unique, contemporary corporate dynamics that traditional structural models often overlook. These findings imply that corporate executives in the consumer cyclicals sector should prioritize liquidity optimization and agile working capital management over aggressive, debt-fueled asset expansion, as strategic cash control offers a more dependable path to profitability during uncertain market cycles.